Soft Skills: The Invisible Engine of Success in the Professional and Organizational World - de Lorenzo Ros, Sara; González Rico, Pablo; Atanes Torres, Roberto (Street Art & Urban Creativity, 2025)
The aim of this study is to explore the soft skills that are most closely related to the ability to respond to activities or tasks in the work environment. The sample is made up of 530 employees who are assessed on 11 competencies distributed over 24 differentiated dimensions. The results show that the sample can be grouped into three significantly differentiated clusters, one of which stands out because it is the one most valued by organisations. It also focuses on the areas of training for development, professional performance and employability. It highlights the competencies of empathy, involvement, commitment, responsibility and autonomy as the backbone of the three clusters. Finally, the results are interpreted, highlighting their applicability in the business market.